Negative active material as well as preparation method and application thereof
By covering the optimized carbon film layer on the silicon oxygen compound negative electrode material, the problem of unstable irreversible substances and interfacial reactions in the prior art during the lithium embedding process is solved, and higher cycle stability and high temperature performance are achieved, reducing expansion and gas production.
Patent Information
- Application Number
- CN202510125570.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-02
- Publication Date
- 2025-04-08
AI Technical Summary
The existing silicon oxygen compound negative electrode materials are prone to generate thick SEI films and irreversible deliquency substances when the lithium is first embedded, resulting in low first-time Coulomb efficiency of lithium-ion batteries, limiting the improvement of the energy density of the entire battery, and at the same time there are problems of low circulation efficiency, large expansion and safety risks.
The negative electrode active material containing a silicon-based material core and a carbon film layer covering the carbon film layer is adopted. The silicon-based material core contains silicon oxygen compounds, and the thickness and mass ratio of the carbon film layer are optimized by controlling the ratio of the median particle size and specific surface area to reduce the defects of the carbon film layer.
It improves the interface stability of the negative electrode active material, enhances cycling stability, high temperature performance, reduces expansion and gas production, and improves the overall performance of lithium-ion batteries.
Smart Images

Figure CN119786584A_ABST
Abstract
Description
[0001] This application is a divisional application of the Chinese patent application with the invention name “A negative electrode active material, its preparation method and application”, application number 202210197761.5 and application date March 2, 2022. Technical Field
[0002] The present application relates to the field of batteries, and in particular, to a negative electrode active material for a secondary battery, a preparation method thereof, an electrode and a battery. Background Art
[0003] At present, there are three main types of silicon negative electrode active materials: one is single silicon (including nano silicon, porous silicon, amorphous silicon, etc.) and its composite materials with carbon materials; the second is alloy materials composed of silicon and other metals (such as iron, manganese, nickel, chromium, cadmium, tin, copper, etc.) and non-metals (carbon, nitrogen, phosphorus, boron, etc.); the third is silicon oxide compounds and their composite materials with carbon materials. However, due to many reasons of single silicon itself, the first and second materials have poor cycle performance of the electrode materials obtained, and are easy to pulverize and separate from the current collector.
[0004] Since silicon oxide compounds contain more inactive substances, their capacity is lower than that of single silicon negative electrode active materials; however, at the same time, due to the presence of these inactive components, the expansion of silicon during the cycle is effectively suppressed by the inactive phase, so its cycle stability has obvious advantages.
[0005] Silicon oxide compounds also have their own specific problems. When the material is first embedded with lithium, a thicker SEI film is often formed on the surface of the particles due to many side reactions with the electrolyte; at the same time, substances such as lithium silicate and lithium oxide that cannot be reversibly delithiated are generated inside the particles, causing irreversible loss of lithium ions in the battery. The above two types of irreversible reactions lead to a low initial coulombic efficiency of lithium-ion batteries containing silicon oxide negative electrodes, thereby limiting the improvement of the energy density of the entire battery. In addition, silicon oxide compounds also have problems such as low ionic and electronic conductivity and low coulombic efficiency during battery cycling.
[0006] On the other hand, a large number of research works have found that the surface of silicon oxide compound particles has a significant effect on the stability of their electrochemical properties, including the interfacial reaction stability between the surface of silicon oxide particles and the electrolyte, and the sensitivity of the surface of silicon oxide particles to the precipitation of transition metals. The above-mentioned interfacial stability significantly affects the cycle life of silicon-containing battery systems, charging and discharging in high temperature environments, storage stability, and battery cell expansion. Due to the existence of interfacial side reactions, the battery cell may also experience serious gas production after undergoing multiple charge and discharge cycles or being exposed to high temperature environments, posing a safety risk. Therefore, the preparation of silicon oxide compound particles with stable surface characteristics is one of the key issues that the industry urgently needs to solve.
[0007] The contents of the background technology section are merely the technologies known to the applicant and do not represent the prior art in the field. Summary of the invention
[0008] In order to solve at least one of the above technical problems, the present invention provides a negative electrode active material, which comprises negative electrode active material particles, wherein the negative electrode active material particles include a silicon-based material core and a carbon film layer covering the surface of the silicon-based material core; the silicon-based material core comprises a silicon-oxygen compound;
[0009] The median particle size D of the negative electrode active material 50 and calculate the particle size D c The ratio satisfies: D 50 / D c ≤15, wherein the calculated particle size D c =7×A / S, A is the particle size distribution span of the negative electrode active material, and S is the specific surface area of the negative electrode active material.
[0010] In some embodiments of the present invention, the median particle size D of the negative electrode active material is 50 and calculate the particle size D c The ratio satisfies: D 50 / D c ≤10, preferably D 50 / D c ≤5, further preferred D 50 / D c ≤2.5.
[0011] In some embodiments of the present invention, the specific surface area S of the negative electrode active material is 0.1-15m 2 / g, preferably 0.3-10m 2 / g, more preferably 0.3-6m 2 / g.
[0012] In some embodiments of the present invention, the median particle size D of the negative electrode active material is 50 0.2-20 μm, preferably 1-15 μm, more preferably 3-13 μm;
[0013] The particle size distribution span value A of the negative electrode active material is ≤2.0, preferably ≤1.5, and more preferably ≤1.2.
[0014] In some embodiments of the present invention, the silicon-based material core further contains lithium.
[0015] In some embodiments of the present invention, the lithium content in the negative electrode active material particles is 0.1-20 wt %, preferably 2-18 wt %, and more preferably 4-15 wt %.
[0016] In some embodiments of the present invention, the silicon content in the negative electrode active material particles is 30-80wt%, preferably 35-65wt%, and more preferably 40-65wt%.
[0017] In some embodiments of the present invention, the negative electrode active material particles further include elemental silicon nanoparticles, and the median particle size of the elemental silicon nanoparticles dispersed in the core of the silicon-based material is between 0.1-35 nm, preferably 0.5-20 nm, and more preferably 1-15 nm.
[0018] In some embodiments of the present invention, the thickness of the carbon film layer is 0.001-5 μm, preferably 0.005-2 μm, and more preferably 0.01-1 μm.
[0019] In some embodiments of the present invention, the mass proportion of the carbon film layer is 0.01-20wt% of the total mass of the negative electrode active material particles, preferably 0.1-15wt%, and more preferably 1-12wt%.
[0020] The present invention also provides an electrode, which comprises the above negative electrode active material.
[0021] The present invention also provides a battery, which comprises the above electrode.
[0022] The present invention also provides a method for preparing the above-mentioned negative electrode active material, comprising:
[0023] preparing silicon oxide particles; and
[0024] A carbon film layer is coated on the surface of the silicon oxide compound particles.
[0025] In some embodiments of the present invention, the above method further includes:
[0026] The silicon oxide compound particles coated with the carbon film layer are doped with lithium.
[0027] The carbon film layer of the negative electrode active material provided by the present invention has fewer defects, higher interface stability in the electrochemical system, and has more excellent cycle stability, high temperature performance, and lower expansion and gas generation.
[0028] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 A flow chart of a preparation process provided for one embodiment of the present invention.
[0030] Figure 2A preparation process flow chart provided for another embodiment of the present invention. DETAILED DESCRIPTION
[0031] The following is a more detailed description of the specific embodiments of the present invention in conjunction with the accompanying drawings and examples, so that the scheme of the present invention and its advantages in various aspects can be better understood. However, the specific embodiments and examples described below are only for the purpose of illustration, rather than for limiting the present invention.
[0032] It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0033] [Negative electrode active material]
[0034] The present invention provides a negative electrode active material for a battery, which has negative electrode active material particles. The negative electrode active material particles contain a silicon-based material core and a carbon film layer covering the surface of the silicon-based material core. The silicon-based material core contains silicon oxide compounds, and the silicon-based material core can be silicon oxide compound particles or silicon oxide compound particles embedded with lithium, that is, the silicon-based material core can also contain lithium elements.
[0035] The median particle size D of the negative electrode active material provided by the present invention is 50 and calculate the particle size D c The ratio satisfies: D 50 / D c ≤15, where the particle size D is calculated c =7×A / S, A is the particle size distribution span of the negative electrode active material, and S is the specific surface area of the negative electrode active material. 90 -D 10 ) / D 50 , where particle size D 10 The median particle size D is the particle size at which the cumulative distribution of particles is 10%, that is, the volume content of particles smaller than this particle size accounts for 10% of all particles; 50 The particle size at which the cumulative distribution of particles is 50%, that is, 50% of the particles exceed this value and 50% of the particles are below this value; particle size D 90 It is the particle size at which the cumulative distribution of particles is 90%, that is, the volume content of particles smaller than this particle size accounts for 90% of all particles.
[0036] The inventors of the present invention have found in their research that the surface properties of the negative electrode active material particles used in batteries, especially their interface stability in the electrochemical system, have a significant correlation with the structure of the carbon film layer coated on their surface.
[0037] Common structural defects of carbon film layers include pores, impurities, disordered carbon layer crystal structure, more carbon-hydrogen / carbon-oxygen / carbon-sulfur bonds, high surface wrinkles, cracks, etc. The above structural defects may lead to an increase in the specific surface area of the negative electrode active material, more side reactions with the electrolyte, and stronger interactions with the transition metal dissolved from the positive electrode, which deteriorates the electrochemical properties of the negative electrode active material, such as cycle stability, high temperature stability, and expansion rate. Due to the existence of interfacial side reactions, the battery cell may also experience severe flatulence after cycling or in a high temperature environment, posing a safety risk.
[0038] The median particle size D of the negative electrode active material provided by the present invention is 50 and calculate the particle size D c The ratio satisfies: D 50 / D c ≤15, at this time, the carbon film layer has fewer defects, so the interface stability is higher in the electrochemical system, and it has better cycle stability, high temperature performance and lower expansion and gas production.
[0039] In some embodiments of the present invention, D 50 / D c ≤10, preferably D 50 / D c ≤5, further preferred D 50 / D c ≤2.5. The smaller the value, the smaller the defects of the carbon film layer on the surface of the negative electrode active material.
[0040] In some embodiments of the present invention, the specific surface area S of the negative electrode active material is 0.1-15 m 2 / g, preferably 0.3-10m 2 / g, more preferably 0.3-6m 2 / g.
[0041] In some embodiments of the present invention, the median particle size D of the negative electrode active material is 50 It is 0.2-20 μm, preferably 1-15 μm, and more preferably 3-13 μm.
[0042] In some embodiments of the present invention, the particle size distribution span value A of the negative electrode active material is ≤2.0, preferably ≤1.5, and more preferably ≤1.2.
[0043] In some embodiments of the present invention, the silicon content in the negative electrode active material particles may be 30-80wt%, preferably 35-65wt%, and further preferably 40-65wt%, so that the material has a very high reversible capacity.
[0044] In some embodiments of the present invention, the lithium content in the core of the silicon-based material may be 0.1-20 wt %, preferably 2-18 wt %, and more preferably 4-15 wt %.
[0045] In some embodiments of the present invention, the negative electrode active material particles also contain single nano silicon. It can be evenly dispersed in the core of the silicon-based material. Among them, the single nano silicon can exist in the core of the silicon-based material in the form of nanoparticles, and the median particle size can be between 0.1-35nm, preferably 0.5-20nm, and more preferably 1-15nm. When the particles within this particle size range undergo the cycle of lithium ion insertion and extraction, the particles expand less and are not easy to break, so that the cycle expansion of the lithium ion secondary battery using this material is small and the cycle is stable.
[0046] In some embodiments of the present invention, the thickness of the carbon film layer may be between 0.001-5 μm, preferably between 0.005-2 μm, and more preferably between 0.01-1 μm. The presence of the carbon film layer can effectively improve the conductivity of the particles, reduce the contact resistance between particles in the negative electrode sheet, the negative electrode sheet and the current collector, thereby improving the lithium extraction efficiency of the material, reducing the polarization of the lithium-ion battery and promoting its cycle stability.
[0047] In some embodiments of the present invention, the mass proportion of the carbon film layer may be 0.01-20 wt %, preferably 0.1-15 wt %, and more preferably 1-12 wt % of the total mass of the negative electrode active material particles.
[0048] The negative electrode active material for the battery provided in the present application has relatively stable surface properties, so its interface stability with the electrolyte is high and its interaction with the transition metal precipitated from the positive electrode is less. The battery prepared using this negative electrode active material has the advantages of stable cycle, excellent high temperature performance, low expansion and low gas production.
[0049]
Method for preparing negative electrode active material
[0050] Figure 1 The figure is a flow chart of a process for preparing a negative electrode active material according to an exemplary embodiment of the present invention.
[0051] S101: preparing silicon oxide particles.
[0052] The specific process of preparation can be carried out in the following steps:
[0053] First, in an inert gas atmosphere or under reduced pressure, a mixture of metal silicon powder and silicon dioxide powder is heated in a temperature range of 900°C-1600°C to generate silicon oxide gas. The molar ratio of metal silicon powder to silicon dioxide powder is set in the range of 0.5-1.5. The gas generated by the heating reaction of the raw materials will be deposited on the adsorption plate. When the temperature in the reactor is reduced to below 100°C, the sediment is taken out and crushed and powdered using equipment such as a ball mill and a jet mill to obtain silicon oxide compound particles.
[0054] The silicon oxide compound particles referred to in the present invention include silicon oxide (silicon monoxide and / or silicon dioxide) materials. In an exemplary embodiment of the present invention, the silicon oxide stoichiometric ratio in the silicon oxide compound particles may be 1:0.4-1:2, optionally 1:0.6-1:1.5, and further optionally 1:0.8-1:1.2. Of course, in addition to silicon oxide, there may be other trace impurity elements.
[0055] S102: coating the surface of the silicon oxide compound particles with a carbon film layer.
[0056] The structure of the carbon film layer on the particle surface is closely related to its preparation process. The carbon film layers obtained under different process parameters (such as carbon source type, coating temperature, atmosphere, gas pressure, heating rate, carbon content, magnetic field, electric field, etc.) and different furnace structure designs have significant structural differences, and the degree of their defects is also significantly different.
[0057] According to an exemplary embodiment, the silicon oxide compound may be a non-disproportionated silicon oxide compound or a disproportionated heat treated silicon oxide compound, wherein the disproportionated heat treatment temperature may be 600-1100°C, optionally 700-1000°C, and more preferably 800-1000°C.
[0058] In the present invention, the carbon film layer can be directly obtained by chemical vapor deposition (CVD). The carbon source used by CVD is a hydrocarbon gas, and the decomposition temperature of the hydrocarbon gas can be 600-1100°C, preferably 700-1000°C, and more preferably 800-1000°C. In the above-mentioned carbon film coating process, the selection of the carbon source, the carbonization temperature, the amount of carbon source added, the ratio of the gas and the flow rate have a significant effect on the structure of the final carbon film. In addition, by controlling the gas pressure (vacuum degree) and the atmosphere ratio during the growth process of the carbon film, and designing a unique gas flow direction, the structure of the carbon film is also significantly affected. Preferably, a mixture of carbon source gas and inert gas or reducing gas (such as argon, nitrogen, helium, hydrogen, etc.) is introduced in a certain proportion, and the quality of the carbon film obtained is better than that of only introducing pure carbon source gas. Further, controlling the volume proportion of the carbon source gas in the mixed gas to be no more than 90%, preferably no more than 75%, and more preferably no more than 65%, is conducive to obtaining a carbon film layer with better coating quality and better uniformity. In addition, lowering the furnace gas pressure during the carbon film growth process to maintain a certain degree of negative pressure (vacuum) can also greatly increase the uniformity of the carbon film layer and obtain a carbon film layer with higher smoothness and density.
[0059] The carbon film layer can also be obtained by first performing carbon reaction coating and then performing heat treatment carbonization in a non-oxidizing atmosphere. The carbon reaction coating method can use any one of a mechanical fusion machine, a VC mixer, a coating kettle, a spray dryer, a sand mill or a high-speed disperser. The solvent used during coating is a combination of one or more of water, methanol, ethanol, isopropanol, n-butanol, ethylene glycol, ether, acetone, N-methylpyrrolidone, methyl butyl ketone, tetrahydrofuran, benzene, toluene, xylene, N,N-dimethylformamide, N,N-dimethylacetamide, and chloroform. The carbon source can be a combination of one or more of coal tar, petroleum asphalt, polyvinyl alcohol, epoxy resin, polyacrylonitrile, polymethyl methacrylate, glucose, sucrose, polyacrylic acid, and polyvinyl pyrrolidone. The equipment used for heat treatment carbonization can be any one of a rotary kiln, a ladle furnace, a roller kiln, a push plate kiln, an atmosphere box furnace or a tube furnace. The temperature of the heat treatment carbonization can be 600-1100°C, preferably 700-1000°C, more preferably 800-1000°C, and the insulation time is 0.5-24 hours. The non-oxidizing atmosphere can be provided by at least one of the following gases: nitrogen, argon, hydrogen or helium. In the above-mentioned carbon film coating process, the selection of the carbon source, the carbonization temperature, the amount of carbon source added, the heating rate, the design of the heating and insulation program, the intensity of mechanical stirring and the selection of coating equipment all have a significant effect on the structure of the final carbon film. Preferably, designing a multi-stage insulation heating program is conducive to obtaining a better quality carbon film coating structure. Selecting a suitable intermediate insulation program allows the carbon source compound to be fully melted, have suitable fluidity, and undergo a preliminary coke removal reaction, which is conducive to obtaining a more uniform and dense carbon film coating layer. In addition, during the heat treatment carbonization process, dynamic carbonization is preferred, that is, the material is dynamically stirred during the heating and insulation process to promote the effective discharge of volatiles during the carbonization of the carbon source, which is also conducive to obtaining a carbon film layer with a tighter structure and fewer defects.
[0060] Figure 2 The preparation process of the negative electrode active material of another exemplary embodiment of the present invention is shown. The process comprises the following steps:
[0061] S201: preparing silicon oxide particles.
[0062] S202: coating the surface of the silicon oxide compound particles with a carbon film layer.
[0063] S203: lithium-doping the silicon oxide particles coated with the carbon film layer.
[0064] In the present invention, the silicon oxide particles can be doped (embedded with lithium) by electrochemical doping, liquid phase doping, thermal doping, etc. The lithium doping atmosphere is a non-oxidizing atmosphere, which is composed of at least one of nitrogen, argon, hydrogen or helium.
[0065] The method of embedding lithium element (lithium doping modification method) can be:
[0066] 1) Electrochemical method
[0067] An electrochemical cell is provided, which includes four components: a bath, an anode electrode, a cathode electrode and a power supply, and the anode electrode and the cathode electrode are connected to the two ends of the power supply respectively. At the same time, the anode electrode is connected to a lithium source, and the cathode electrode is connected to a container containing silicon oxide particles. The bath is filled with an organic solvent, so that the lithium source (anode electrode) and the container containing silicon oxide particles (cathode electrode) are immersed in the organic solvent. After the power supply is turned on, due to the occurrence of electrochemical reactions, lithium ions are embedded in the silicon oxide structure to obtain lithium-doped silicon oxide particles. The above-mentioned organic solvent can be ethylene carbonate, propylene carbonate, butylene carbonate, fluoroethylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethyl acetate, propyl acetate, ethyl propionate, propyl propionate, dimethyl sulfoxide and the like. In addition, the organic solvent also contains electrolyte lithium salts, which can be lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), etc. The above-mentioned lithium source (anode electrode) can be lithium foil, or a lithium compound, such as lithium carbonate, lithium oxide, lithium hydroxide, lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium vanadium phosphate, lithium nickel oxide, etc.
[0068] 2) Liquid phase doping method
[0069] Add metallic lithium, electron transfer catalyst, and silicon oxide particles to an ether-based solvent, and continue stirring and heating in a non-oxidizing atmosphere to maintain a constant temperature reaction until the metallic lithium in the solution completely disappears. Under the action of the electron transfer catalyst, metallic lithium can be dissolved in the ether-based solvent and form a coordination compound of lithium ions, which has a lower reduction potential, so it can react with silicon oxides, and lithium ions enter the structure of silicon oxides. The electron transfer catalyst includes biphenyl, naphthalene, etc. The ether-based solvent includes methyl butyl ether, ethylene glycol butyl ether, tetrahydrofuran, ethylene glycol dimethyl ether, etc. The constant temperature reaction temperature is 25-200°C. The non-oxidizing atmosphere is provided by at least one of the following gases: nitrogen, argon, hydrogen or helium.
[0070] 3) Thermal doping method
[0071] The silicon oxide compound particles are uniformly mixed with the lithium-containing compound, and then heat-treated in a non-oxidizing atmosphere. The lithium-containing compound includes lithium hydroxide, lithium carbonate, lithium oxide, lithium peroxide, lithium hydride, lithium nitrate, lithium acetate, lithium oxalate, etc. The mixing method adopts any one of a high-speed disperser, a high-speed stirring mill, a ball mill, a conical mixer, a spiral mixer, a stirring mixer or a VC mixer. The equipment used for the heat treatment is any one of a rotary furnace, a ladle furnace, a liner furnace, a roller kiln, a push plate kiln, an atmosphere box furnace or a tube furnace. The temperature of the heat treatment is 400-850°C, preferably 550-800°C; the insulation time is 1-12 hours; the heating rate is greater than 0.1°C per minute and less than or equal to 10°C per minute. The non-oxidizing atmosphere is provided by at least one of the following gases: nitrogen, argon, hydrogen or helium.
[0072] The step of embedding lithium elements is carried out after coating the carbon film layer, which can inhibit the growth of silicon grains in the silicon oxide compound during the heat treatment process. As a result, nano-scale elemental silicon particles are evenly dispersed and fixed in the lithium silicate compound or silicon oxide compound matrix, which can effectively inhibit the expansion of silicon nanoparticles and prevent silicon particles from gradually melting into larger particles during the charging and discharging process, thereby reducing the expansion deformation of the battery during the cycle and reducing the electrical failure of the silicon material, so that the cycle expansion of the lithium ion secondary battery using this material is small and the cycle is stable. In addition, the step of coating the carbon film layer is carried out before embedding lithium elements, which is conducive to obtaining a carbon film layer with better quality and more complete coating.
[0073] At the same time, the process of embedding lithium elements will have different degrees of influence on the carbon film structure on the surface of silicon oxide particles. If the diffusion process is mild and controllable, it will have little effect on the carbon film structure on the particle surface; if the diffusion process is relatively intense, it can cause changes in the carbon film structure. [Characterization method of negative electrode active materials]:
[0074] 1. Material testing: The following equipment was used to characterize the negative electrode active materials prepared in each embodiment and comparative example: Dandong BetterSize 2000 laser particle size analyzer was used to test the particle size distribution of the negative electrode active materials. Hitachi SU8010 scanning electron microscope (SEM) was used to observe the surface morphology of the negative electrode active materials. Quantachrome Instruments NOVA 4200e specific surface area tester was used to test the specific surface area of the negative electrode active materials. The specific surface area test requirements are as follows: Weigh the sample with a sample tube, use nitrogen, and use a multi-point method to test the specific surface area of the sample in the relative pressure range of p / p0=0.05-0.3.
[0075] 2. Slurry and pole piece preparation: Take 30 parts of the above-mentioned negative electrode active material, 64 parts of artificial graphite, 2.5 parts of conductive additives, and 3.5 parts of binder, and apply the slurry in an aqueous system, then dry and roll to obtain a negative electrode pole piece containing the negative electrode active material of the present application.
[0076] 3. Full battery evaluation: The negative electrode sheets of the negative electrode active materials prepared in each embodiment and comparative example are cut, vacuum baked, wound together with the paired ternary positive electrode sheets and separators and loaded into an aluminum plastic shell of corresponding size, a certain amount of electrolyte is injected and degassed and sealed, and a lithium-ion full battery of about 3.2Ah is obtained after formation. The full battery was fully charged and stored for 60 days at 60°C. The thermal expansion rate, capacity retention rate and capacity recovery rate of the system after high-temperature full-charge storage were tested to evaluate the high-temperature storage stability of the system. The test method for the thermal expansion rate is as follows: after the battery cell is fully charged and stored at 60°C for 60 days, the battery cell is taken out and immediately tested. The thickness of the battery cell is d, where the thickness of the initial half-charge state of the battery cell is d0, and the thermal expansion rate = (d-d0) / d0. After cooling, the battery cell is placed on the Xinwei battery test system for discharge test, the discharge capacity is D1, the discharge capacity of the battery cell before high temperature storage is D0, and the capacity retention rate = D1 / D0. Then the battery cell is subjected to a charge-discharge cycle again, the discharge capacity is D2, and the capacity recovery rate = D2 / D0.
[0077] The present application is further described below in conjunction with specific embodiments.
[0078] Example 1-1
[0079] After 1000g of silicon oxide particles with a median particle size of 6μm (silicon-oxygen atomic ratio of 1:1) and low-temperature coal tar powder are dry-mixed in a coating kettle, 2000g of dimethylformamide is added while stirring, and the mixed powder is evenly dispersed in dimethylformamide. The coating kettle is then heated to 340°C and kept stirring at a constant temperature for 3 hours to obtain a silicon oxide material coated with coal tar. The above material is statically heated to 680°C under a nitrogen atmosphere and kept for 4 hours to carbonize the coal tar. The material obtained after cooling is passed through a 500-mesh sieve to obtain a carbon film-coated silicon oxide powder. The carbon film-coated silicon oxide powder is tested for carbon content, and the carbon content is 7wt%.
[0080] The above steps result in a specific surface area S of the negative electrode active material = 15 m 2 / g, median particle size D of the product 50 The particle size distribution span is A=1.52, and the particle size D is calculated based on the specific surface area. c = 0.71 μm, so the median particle size D 50 and calculate the particle size Dc The ratio is 15.
[0081] Take 30 parts of the above-mentioned negative electrode active material, 64 parts of artificial graphite, 3.5 parts of conductive additives, and 2.5 parts of binder, apply slurry in an aqueous system, and then dry and roll to obtain a silicon-containing negative electrode sheet.
[0082] In this embodiment, the high-temperature storage evaluation results of the full battery containing the negative electrode active material are as follows: after 60 days of high-temperature storage at 60°C with full charge, the thermal expansion rate of the battery cell is 22.7%, the battery cell has floating air, and the capacity retention rate after high-temperature storage is 78.6%, and the capacity recovery rate is 86.3%.
[0083] Example 1-2
[0084] The process is similar to that of Example 1-1, except that the carbonization temperature of the coal tar is adjusted to 780°C, and the carbon content remains at 7wt%.
[0085] Please see Table 1 for performance parameters.
[0086] Examples 1-3
[0087] 1000g of silicon oxide particles with a median particle size of 9μm and medium-temperature coal tar powder were dry mixed in a VC reactor, and then directly heated to 720°C and kept stirring at a constant temperature for 4 hours to carbonize the coal tar in situ. The material obtained after cooling was passed through a 500-mesh sieve to obtain a carbon film-coated silicon oxide powder. The carbon content of the carbon film-coated silicon oxide powder was tested, and the carbon content was 7wt%.
[0088] The performance parameters and high temperature storage performance of the battery cell using the negative electrode active material are shown in Table 1.
[0089] Examples 1-4
[0090] After 1000g of silicon oxide particles with a median particle size of 8μm and high-temperature coal tar powder are dry-mixed in a VC reactor, they are heated to 450℃ and stirred at a constant temperature for 3 hours to allow the coal tar to have sufficient fluidity to achieve uniform coating, and then heated to 780℃ and kept warm for 5 hours for carbonization. During the carbonization process, sufficient stirring is still maintained to promote the effective discharge of volatiles during the asphalt carbonization process, resulting in a more compact carbon film layer. The material obtained after cooling is passed through a 500-mesh sieve to obtain a carbon film-coated silicon oxide powder. The carbon content of the carbon film-coated silicon oxide powder is tested, and the carbon content is 6wt%.
[0091] The performance parameters and high temperature storage performance of the battery cell using the negative electrode active material are shown in Table 1.
[0092] Examples 1-5
[0093] 1000 g of silicon oxide particles with a median particle size of 7 μm were weighed and placed in a CVD furnace. Methane was used as a carbon source and the coating reaction was carried out at 800°C, wherein the flow ratio of methane to argon was 1:1, to obtain silicon oxide particles coated with a carbon film layer. The carbon content of the silicon oxide powder coated with the carbon film was tested, and the carbon content was 5wt%.
[0094] The performance parameters and high temperature storage performance of the battery cell using the negative electrode active material are shown in Table 1.
[0095] Examples 1-6
[0096] 1000 g of silicon oxide particles with a median particle size of 10 μm were weighed and placed in a CVD furnace. Methane was used as a carbon source and the coating reaction was carried out at 800°C, wherein the flow ratio of methane to argon was 2:1, to obtain silicon oxide particles coated with a carbon film layer. The carbon content of the silicon oxide powder coated with the carbon film was tested, and the carbon content was 7 wt%.
[0097] The performance parameters and high temperature storage performance of the battery cell using the negative electrode active material are shown in Table 1.
[0098] Examples 1-7
[0099] Weigh 1000 grams of silicon oxide particles with a median particle size of 6 μm and place them in a CVD furnace. Use methane as a carbon source and carry out a low-pressure coating reaction at 800°C, where the flow ratio of methane to argon is 2:1. Although the production efficiency of the low-pressure CVD reaction is low, it can greatly increase the uniformity of the carbon film layer, and obtain a carbon film layer with higher smoothness and density and fewer defects. The carbon content of the silicon oxide powder coated with the carbon film was tested, and the carbon content was 7wt%.
[0100] The performance parameters and high temperature storage performance of the battery cell using the negative electrode active material are shown in Table 1.
[0101] Examples 1-8
[0102] 1000 g of silicon oxide particles with a median particle size of 5 μm were weighed and placed in a CVD furnace. Methane was used as a carbon source and the coating reaction was carried out at 800°C, wherein the flow ratio of methane to argon was 0.6:1, to obtain silicon oxide particles coated with a carbon film layer. The carbon content of the silicon oxide powder coated with the carbon film was tested, and the carbon content was 6wt%.
[0103] The performance parameters and high temperature storage performance of the battery cell using the negative electrode active material are shown in Table 1.
[0104] Examples 1-9 to 1-17
[0105] Similar to Examples 1-1 to 1-8, silicon oxide compound particles are used as raw materials and different carbon film coating processes are adopted, including adjusting the selection of carbon source, carbonization temperature, amount of carbon source added, air pressure (vacuum degree), atmosphere ratio, airflow direction, as well as heating rate, design of heating and insulation procedures, intensity of mechanical stirring, selection of equipment, etc., to obtain silicon oxide compound powders coated with different carbon films of Examples 1-9 to 1-17.
[0106] The performance parameters and high temperature storage performance of the battery cell using the negative electrode active material are shown in Table 1.
[0107] Comparative Example 1-1
[0108] 1000g of silicon oxide compound particles and sucrose were dry mixed in a coating kettle, then heated to 200°C and stirred for 3 hours, and then heated to 500°C and kept for 5 hours for carbonization. The material obtained after cooling was passed through a 500-mesh sieve to obtain a carbon film-coated silicon oxide compound powder. The carbon content of the carbon film-coated silicon oxide compound powder was tested, and the carbon content was 10wt%.
[0109] The performance parameters and high temperature storage performance of the battery cell using the negative electrode active material are shown in Table 1.
[0110] Comparative Example 1-2
[0111] 1000g of silicon oxide particles and sucrose were dry mixed in a coating kettle, then heated to 180°C and stirred for 3 hours, and then heated to 400°C for 8 hours for carbonization. The material obtained after cooling was passed through a 500-mesh sieve to obtain a carbon film-coated silicon oxide powder. The carbon content of the carbon film-coated silicon oxide powder was tested, and the carbon content was 8wt%.
[0112] The performance parameters and high temperature storage performance of the battery cell using the negative electrode active material are shown in Table 1.
[0113] Table 1
[0114]
[0115]
[0116] From Table 1, we can see that the median particle size D of the negative electrode active material 50 and calculate the particle size D c The ratio D 50 / D c The smaller it is, the better the high-temperature stability of the negative electrode active material is, the smaller the expansion is, and the less likely it is to produce gas.
[0117] Furthermore, it can be seen from Table 1 that the carbon film layers obtained under different process parameters (such as carbon source type, coating temperature, atmosphere, gas pressure, heating rate, carbon content, heating and insulation program, mechanical stirring, etc.) and different furnace structure designs have significant structural differences, and the degree of their defects is also significantly different.
[0118] Example 2-1
[0119] The negative electrode active material of Example 1-16 is used as a raw material, the powder, the metal lithium strip and the biphenyl are added into a sealable glass container, and then methyl butyl ether is added and stirred to react under an argon atmosphere. After the reaction is completed and dried, the obtained powder is placed in an argon atmosphere for heat treatment, and the temperature is increased to 680°C at a heating rate of 2°C per minute, and then kept warm for 10 hours, and then naturally cooled to obtain lithium-doped silicon oxide compound powder.
[0120] The performance parameters and high temperature storage performance of the battery cell using the negative electrode active material are shown in Table 2.
[0121] Example 2-2
[0122] The product of Example 1-16 is used as the raw material, similar to Example 2-1, but the heat treatment process after lithium doping is changed to: heating to 720°C at a heating rate of 5°C per minute, then keeping warm for 3 hours, and then naturally cooling to obtain lithium-doped silicon oxide powder.
[0123] The performance parameters and high temperature storage performance of the battery cell using the negative electrode active material are shown in Table 2.
[0124] Example 2-3
[0125] The product of Example 1-16 is used as the raw material, similar to Example 2-1, but the heat treatment process after lithium doping is changed to: heating to 720°C at a heating rate of 10°C per minute, then keeping warm for 6 hours, and then naturally cooling to obtain lithium-doped silicon oxide powder.
[0126] The performance parameters and high temperature storage performance of the battery cell using the negative electrode active material are shown in Table 2.
[0127] Embodiment 2-4
[0128] The product of Example 1-16 is used as the raw material, similar to Example 2-1, but the heat treatment process after lithium doping is changed to: heating to 850°C at a heating rate of 10°C per minute, then keeping warm for 2 hours, and then naturally cooling to obtain lithium-doped silicon oxide powder.
[0129] The performance parameters and high temperature storage performance of the battery cell using the negative electrode active material are shown in Table 2.
[0130] Embodiment 2-5
[0131] Using the products of Examples 1-10 as raw materials, the above-mentioned particles are mixed with lithium-containing compounds (such as lithium oxide, lithium hydride, lithium hydroxide, lithium carbonate, etc.), and the mixed powder is placed in an argon atmosphere for heat treatment. The temperature is increased to 400°C at a heating rate of 2°C per minute and kept warm for 3 hours, and then the temperature is increased to 650°C and kept warm for 10 hours. After natural cooling, a lithium-containing silicon oxide compound coated with a carbon film is obtained.
[0132] The performance parameters and high temperature storage performance of the battery cell using the negative electrode active material are shown in Table 2.
[0133] Embodiment 2-6
[0134] The product of Example 1-10 is used as raw material, similar to Example 2-5, but the heat treatment process after lithium doping is changed to: directly heat the temperature to 700°C at a heating rate of 5°C per minute, then keep warm for 6 hours, and then naturally cool to obtain lithium-doped silicon oxide compound powder.
[0135] The performance parameters and high temperature storage performance of the battery cell using the negative electrode active material are shown in Table 2.
[0136] Embodiment 2-7
[0137] The product of Example 1-10 is used as raw material, similar to Example 2-5, but the heat treatment process after lithium doping is changed to: directly heat the temperature to 820°C at a heating rate of 10°C per minute, then keep warm for 2 hours, and then naturally cool to obtain lithium-doped silicon oxide compound powder.
[0138] The performance parameters and high temperature storage performance of the battery cell using the negative electrode active material are shown in Table 2.
[0139] Table 2
[0140]
[0141] Combining the data in Table 1 and Table 2, it can be seen that the process of embedding lithium elements will have different degrees of influence on the carbon film structure on the surface of silicon oxide particles. If the diffusion process is mild and controllable, it will have little effect on the carbon film structure on the surface of the particles. If the diffusion process is relatively intense, it can cause changes in the carbon film structure, which reduces the interface stability of the material, resulting in a decrease in the high-temperature storage performance of the battery using the negative electrode active material and an increase in expansion.
[0142] Obviously, the above embodiments are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the protection scope of the present invention.
Claims
1. A negative electrode active material, comprising negative electrode active material particles, characterized in that: The negative electrode active material particles include a silicon-based material core and a carbon film layer covering the surface of the silicon-based material core; the silicon-based material core contains silicon oxide and lithium element; The median particle size D of the negative electrode active material 50 and calculate the particle size D c The ratio satisfies: D 50 / D c ≤15, wherein the calculated particle size D c =7×A / S, A is the particle size distribution span of the negative electrode active material, and S is the specific surface area of the negative electrode active material; Wherein, the doping of the lithium element includes heat treatment, and the heating rate of the heat treatment is less than or equal to 10° C. / min.
2. The negative electrode active material according to claim 1, characterized in that The median particle size D of the negative electrode active material 50 and calculate the particle size D c The ratio satisfies: D 50 / D c ≤10, preferably D 50 / D c ≤5, further preferred D 50 / D c ≤2.
5.
3. The negative electrode active material according to claim 1, characterized in that The specific surface area S of the negative electrode active material is 0.1-15 m 2 / g, preferably 0.3-10m 2 / g, more preferably 0.3-6m 2 / g.
4. The negative electrode active material according to claim 1, characterized in that The median particle size D of the negative electrode active material 50 0.2-20 μm, preferably 1-15 μm, more preferably 3-13 μm; The particle size distribution span value A of the negative electrode active material is ≤2.0, preferably ≤1.5, and more preferably ≤1.
2.
5. The negative electrode active material according to claim 1, characterized in that The lithium content in the negative electrode active material particles is 0.1-20 wt %, preferably 2-18 wt %, and more preferably 4-15 wt %.
6. The negative electrode active material according to claim 1, characterized in that The silicon content in the negative electrode active material particles is 30-80 wt %, preferably 35-65 wt %, and more preferably 40-65 wt %.
7. The negative electrode active material according to claim 1, characterized in that The negative electrode active material particles further include elemental silicon nanoparticles, and the median particle size of the elemental silicon nanoparticles dispersed in the core of the silicon-based material is between 0.1-35 nm, preferably 0.5-20 nm, and more preferably 1-15 nm.
8. The negative electrode active material according to claim 1, characterized in that The thickness of the carbon film layer is 0.001-5 μm, preferably 0.005-2 μm, and more preferably 0.01-1 μm. 9 . The negative electrode active material according to claim 1 , wherein the mass proportion of the carbon film layer is 0.01-20 wt %, preferably 0.1-15 wt %, and more preferably 1-12 wt % of the total mass of the negative electrode active material particles.
10. An electrode, characterized in that: The negative electrode active material comprises the negative electrode active material as described in any one of claims 1 to 9.
11. A battery, characterized in that: Comprising the electrode as claimed in claim 10.
12. A method for preparing the negative electrode active material according to claim 1, characterized in that: include: preparing silicon oxide particles; Coating a carbon film layer on the surface of the silicon oxide compound particles; as well as The silicon oxide compound particles coated with the carbon film layer are doped with lithium.